A simulation-based approach for teaching the systems perspective of strategic performance management - Capelo, C.; Lopes, A.; Mata, A. (Accounting Education, 2015)
Kaplan and Norton introduced the balanced scorecard (BSC), which is based on a systems perspective of the business strategy and performance measurement. Many organisations around the world use the BSC to define, implement and manage strategy. Nevertheless, there are studies that identify problems and limitations associated with the implementation and use of the BSC. The contribution of this paper consists of proposing and testing a simulation-based learning strategy for teaching the BSC. An experiment that uses a business simulator tests a set of hypotheses about the influence of simulation on the student understanding of the BSC. The simulation environment involves a mathematical model, a human–computer interface and several functionalities specifically designed to foster student understanding of the BSC concepts. Student feedback indicated that the simulation significantly enhanced the understanding of the BSC concepts related to the strategic management and double-loop learning processes and the systems perspective.